Respuesta :
Answer:
x = 3
y = -1
(3, -1)
Step-by-step explanation:
Substitute the y variable in 3x-5y=14 with the expression x-4
3x - 5y = 14
3x - 5(x - 4) = 14 Use the distributive property
3x - (5x - 20) = 14 Subtract the binomial
3x - 5x + 20 = 14 Collect like terms
20 - 2x = 14 Isolate "x" now
-2x = 14 - 20 Subtract 20 from both sides
-2x = -6 Divide both sides by -2
x = 3 Solved for x
Substitute x using 3 in one of the equations.
y = x - 4
y = 3 - 4 Subtract
y = -1 Solved for y
The solution as an ordered pair (x, y) is (3, -1).
The system would equate to (3,-1). X=3 and y=-1
Substitute is plugging in one value into another equation to solve it. In this system of equations, the value of y is given which can be plugging in to 3x-5y=14.
First plug the value of y in to the equation which will give you 3x-5(x-4)=14. Next you want to distribute -5 to the terms in the parentheses which will leave you with 3x-5x+20=14. Afterwards you want to add like terms and get -2x+20=14. Subtract on both sides by 20 and get -2x=-6, isolate x by dividing by -2 on both sides. X=3.
Now that you have the value of x you need to find the value of y. Plug x into y=x-4 so that you get y=3-4 which will give you y=-1.
Substitute is plugging in one value into another equation to solve it. In this system of equations, the value of y is given which can be plugging in to 3x-5y=14.
First plug the value of y in to the equation which will give you 3x-5(x-4)=14. Next you want to distribute -5 to the terms in the parentheses which will leave you with 3x-5x+20=14. Afterwards you want to add like terms and get -2x+20=14. Subtract on both sides by 20 and get -2x=-6, isolate x by dividing by -2 on both sides. X=3.
Now that you have the value of x you need to find the value of y. Plug x into y=x-4 so that you get y=3-4 which will give you y=-1.